A Partium ábrázolása a történelmi atlaszokban - Suba, János (Közép-Európai Közlemények, 2014)
In our treatise we submit and analise the Partium mapsheets in highschool atlases in Hungary. These atlases were winnowed from the Map Collection of the Museum of Military History. The first atlas in Hungarian language was published by Eduard Hölzer in Vienna. The Hungarian appellation of the atlas was made by György Jausz. The famous wallmaps and historical, geographical atlases made by Manó Kogutowicz were published only later. These atlases were drafted by well-kown contemporary historians and pedagogues (Dezső Csánky, Ignác Goldzieher, Henrik Marczali, Sándor Márki and Gyula Pauer). The mapsheets contained representation of terrain using hachureses. The atlases were used in all schooltypes in Hungary. After World War I, certain atlases and maps were published by the civil–military cartography service. After 1938 the Geographical Institute of the Hungarian Army started to publish maps and atlases for civil purposes. Typical characteristics of these maps were the lack of configurations of terrains and the use of pale colours. The names were easy to read. Some of these atlases were still inuse in both the primary and the secondary education between World War I and II, and even later. Since 1950 the Geographical Institute of the Hungarian Army hasn’t published maps for civil purposes any more. The escalation of keeping information „topsecret” has reached mapmaking, too. Consequently, civil cartography had to be reorganized in the 50’s. The first project of the new Cartographical Company, established in 1954, was to publish a new highschool atlas. The Historical Atlas came out in 1959 to be the first after World War II. This atlas was the product of the theory of class warfare. The information of the Historical Atlas is inferior to those of the maps published between the two wars. There are no county borders and no additional information about the public administration system, in other words, nothing riminds the users to the the 1000 years old Hungarian state. The names are far from being complete, the information included reach the minimum compulsory level only. The historical maps introduced above represent the view on Hungarian history according to the ruling ideology and idealism of the era, as well as the way to spread (forcing) it through teaching history at schools.